Assessment of chronic disease management among patients with diabetes and coronary artery disease receiving care in a cardiology clinic. Issue 2 (28th September 2018) - Pearson, Scott M.; Shakowski, Courtney; Vande Griend, Joseph P.; Page, Robert L.; Khanna, Amber D.; Wright, Garth C.; Saseen, Joseph J.
Abstract : Background: Patients with coronary artery disease (CAD) often have multiple comorbidities (eg, diabetes, hypertension, and hyperlipidemia). It is unclear if these comorbidities are adequately managed among patients established in a cardiology clinic. Methods: This retrospective, observational study used electronic medical record data from 1 January 2014 to 31 October 2017 to examine the achievement of five chronic disease quality measures (glycated hemoglobin, A1C ≤ 9.0%, blood pressure, BP < 140/90 mm Hg, antiplatelet agent, moderate/high‐intensity statin, and annual influenza vaccine). Additional measures of optimal care were also assessed (A1C ≤ 8.0%, A1C ≤ 7.0%, blood pressure < 130/80 mm Hg, high‐intensity statin, pneumococcal polysaccharide vaccination (PPSV23)). Patients were identified from the University of Colorado Health Cardiac and Vascular Center (CVC) with CAD, diabetes, and at least two CVC visits within a 24‐month period (n = 295). Results: The primary outcome measures with highest achievement were for antiplatelet and moderate/high‐intensity statin prescribing (91% and 89%, respectively). The measure with lowest achievement was receipt of influenza vaccination (69%). Women were less likely than men to achieve at least four of the five measures (adjusted odds ratio [OR], 0.44; 95% confidence interval [CI], 0.24‐0.80). Patients with two or more primary care provider (PCP) visits within the past year were more likely to achieve at least four measures compared with patients with less than two PCP visits (adjusted OR, 2.22; 95% CI, 1.14‐4.31). When applying optimal measures, 41% of patients achieved an A1C ≤7%, 52% achieved a blood pressure of <130/80 mm Hg, and 66% were prescribed high‐intensity statins. Conclusions: Achievement for chronic care quality measures was high but performance could be improved, especially among women and patients with infrequent PCP visits. Increased collaboration and communication between primary care and cardiology may improve care for these patients.